Development of a Screening Platform to Identify Small Molecules That Modify ELP1 Pre-mRNA Splicing in Familial Dysautonomia. (January 2019) - Salani, Monica; Urbina, Fabio; Brenner, Anthony; Morini, Elisabetta; Shetty, Ranjit; Gallagher, C. Scott; Law, Emily A.; Sunshine, Sara; Finneran, Dylan J.; Johnson, Graham; Minor, Lisa; Slaugenhaupt, Susan A.
Familial dysautonomia (FD) is an autonomic and sensory neuropathy caused by a mutation in the splice donor site of intron 20 of the ELP1 gene. Variable skipping of exon 20 leads to a tissue-specific reduction in the level of ELP1 protein. We have shown that the plant cytokinin kinetin is able to increase cellular ELP1 protein levels in vivo and in vitro through correction of ELP1 splicing. Studies in FD patients determined that kinetin is not a practical therapy due to low potency and rapid elimination. To identify molecules with improved potency and efficacy, we developed a cell-based luciferase splicing assay by inserting renilla (Rluc) and firefly (Fluc) luciferase reporters into our previously well-characterized ELP1 minigene construct. Evaluation of the Fluc/Rluc signal ratio enables a fast and accurate way to measure exon 20 inclusion. Further, we developed a secondary assay that measures ELP1 splicing in FD patient-derived fibroblasts. Here we demonstrate the quality and reproducibility of our screening method. Development and implementation of this screening platform has allowed us to efficiently screen for new compounds that robustly and specifically enhance ELP1 pre-mRNA splicing.